ПОЗИЦІЯ УЧИТЕЛЯ ДО МІЖОСОБИСТІСНОЇ ВЗАЄМОДІЇ В СИТУАЦІЇ КОНФЛІКТУ (Педагогіка вищої та середньої школи, 2010)
In the article grounds possibilities of the position of teacher to interpersonal interaction in the conflict situation.